Czech cultural standards from Russian perspective in work and study environment - Mikheev, Sergey; Křečková Kroupová, Zuzana, 1972-; Shvechikov, Ivan; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2018)
Russian culture differs from Czech culture, and there are significant differences in the two countries’ cultures. As a result, people coming to the Czech Republic from Russia might find it hard to become integrated effectively in the local environment. The findings of this research should allow understanding better how the process can be eased, and how Russians coming to work or study in the Czech Republic might maximize the effectiveness of their activities through effective cultural understanding. The main aim of this thesis is to identify and describe in detail the Czech cultural standards from the Russian perspective in the study and work environment. The goals of the thesis are to analyze the specificities and characteristics of culture, its elements and models; to reveal the importance of intercultural communication and its forms; to consider the main theories of cultural dimensions, namely the ones developed by G. Hofstede and F. Trompenaars; to focus specifically on the analysis of the Czech Republic, its geography, history, economy and culture. The methodology used for writing this thesis will combine secondary and primary research.
Vedoucí práce: Zuzana Křečková Kroupová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: podniková ekonomika a management [obor dipl. práce]; diplomové práce; master's theses